(untitled) (Eurasian Journal of Learning and Academic Teaching, 2023)
In today’s rapidly evolving world, integrating digital technologies in comprehensive schools has become beneficial and necessary for improving the quality of education. These technologies offer many advantages that enhance students’ learning experience and streamline educators’ administrative tasks. It will discuss the importance and necessity of using digital technologies to improve the quality of education in comprehensive schools.